Implementation of the Islamic Personal Development Program in Developing the Religious Character of Students - Yani, Sisi Putri; Yanti, Winda Kartika; Sartika, Sartika (Al-kayyis: Journal of Islamic Education, 2025)
Abstrak Moral decadence occurring in Integrated Islamic Elementary Schools. There are several students with character issues, whether towards God, their teachers, or their environment. Some students are seen to have difficulty when invited to pray in congregation, shout when talking to their teachers, cheat during exams, litter, and so on. The Islamic Character Development Program is a program established to implement mandatory policies aimed at optimizing Islamic character development among students within educational institutions participating in the program. This study aims to analyze the implementation of the Islamic Character Development Program in developing religious character at the Integrated Islamic Elementary School. This study uses a qualitative descriptive method. Data sources were obtained from 14 informants through in-depth interviews selected using purposive sampling techniques. The results of this study indicate that there are three points discussed in the implementation of the Islamic Character Development Program in developing religious character, namely: i.) The Islamic Personal Development Program is divided into two categories: first, the Islamic Personal Development Program during class hours, and second, the Islamic Personal Development Program outside of class hours. ii.) The implementation of Islamic Personal Development meetings is conducted for one class period per week in each class. The methods used in the Islamic Personal Development Program to cultivate religious character include four approaches: modeling, habit formation, discussion, and lectures or storytelling. These methods are applied in every Islamic Personal Development Program. iii.) Supporting factors include relatively young teachers, a well-structured curriculum, and a sufficiently conducive environment.